2013
DOI: 10.17221/6/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Impact of double Zn and Se biofortification of wheat plants on the element concentrations in the grain

Abstract: Optimisation of the concentrations of essential mineral elements in staple grain diet and reduction in non-essential and potentially toxic elements would considerably alleviate mineral malnutrition and improve the health of humans. Here, wheat (Triticum aestivum L.) plants were biofortified with Zn and/or Se to determine the changes across 36 elements in the grain. The element concentrations were determined by multielemental k 0 -instrumental neutron activation analysis (k 0 -INAA). In comparison to grain from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Many studies have reported that Se uptake of crop could be increased by Se application in wheat (Germ et al 2013), maize (Chilimba et al 2012), rice (Li et al 2010) and other crops (Altansuvd et al 2014). Single effects of foliar spray or application via root of Se on grain Se concentration and yield have been recognized in buckwheat under controlled conditions (Vogrinčič et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported that Se uptake of crop could be increased by Se application in wheat (Germ et al 2013), maize (Chilimba et al 2012), rice (Li et al 2010) and other crops (Altansuvd et al 2014). Single effects of foliar spray or application via root of Se on grain Se concentration and yield have been recognized in buckwheat under controlled conditions (Vogrinčič et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…According to Jiang et al [2015], Se accumulation in common buckwheat was closely associated with the application rate of Se, similarly in case of Germ et al [2013] the increase in Se concentrations in the grain of the double fortified plants was 6-fold greater in comparison to the Se-only bio-fortified plants. According to Poblaciones et al [2013] the difference in concentration between selenite and selenate was more evident as the dose increases.…”
Section: Selenium Contentmentioning
confidence: 97%
“…Also the results of other authors proved dependency of Se content increasing on fertiliser dose. According to Jiang et al [2015], Se accumulation in common buckwheat was closely associated with the application rate of Se, similarly in case of Germ et al [2013] the increase in Se concentrations in the grain of the double fortified plants was 6-fold greater in comparison to the Se-only bio-fortified plants. According to Poblaciones et al [2013] the difference in concentration between selenite and selenate was more evident as the dose increases.…”
Section: Selenium Contentmentioning
confidence: 97%
“…Date of application and dose has to be also very carefully considered, because there is very thin line between toxicity and benefits of Se in human diet. Double biofortification of wheat plants more effectively increases the Se concentrations in the grain, in comparison to single biofortification with Se [Germ et al 2013]. Selenium at low doses has been shown to promote the growth of plants, nevertheless, at high concentrations this metalloid is toxic [Gajewska et al 2013].…”
Section: Introductionmentioning
confidence: 99%